Nosocomial Pneumonia in the Mechanically Ventilated Patient - Fanning, Jonathon; Panigada, Mauro; Li Bassi, Gianluigi (Seminars in Respiratory and Critical Care Medicine, 2022)
Ventilator-associated pneumonia (VAP) is a common complication occurring in critically ill patients who are mechanically ventilated and is the leading cause of nosocomial infection-related death. Etiologic agents for VAP widely differ based on the population of intensive care unit patients, duration of hospital stay, and prior antimicrobial therapy. VAP due to multidrug-resistant pathogens is associated with the highest morbidity and mortality, likely due to delays in appropriate antimicrobial treatment. International guidelines are currently available to guide diagnostic and therapeutic strategies. VAP can be prevented through various pharmacological and non-pharmacological interventions, which are more effective when grouped as bundles. When VAP is clinically suspected, diagnostic strategies should include early collection of respiratory samples to guide antimicrobial therapy. Empirical treatment should be based on the most likely etiologic microorganisms and antibiotics likely to be active against these microorganisms. Response to therapy should be reassessed after 3 to 5 days and antimicrobials adjusted or de-escalated to reduce the burden of the disease. Finally, considering that drug resistance is increasing worldwide, several novel antibiotics are being tested to efficiently treat VAP in the coming decades.
Keywords: ventilator-associated pneumonia; hospital-acquired pneumonia; ventilator-associated event; antibiotic; multidrug resistance; preventive bundle; diagnostic techniques